Mechanical Properties And Microstructure Characterization Of Friction Stir Welded Joint Of Dissimilar Aluminum Alloy AA2024 And AA7050 - et. al., A. Nait Salah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The friction stir welding (FSW) have a wide range of applications in manufacturing industries, aerospace engineering, shipbuilding, and automobile industries. The dissimilar aluminum alloys AA2024 and AA7075 with thickness of 3 mm have been successfully fabricated by FSW with different tool rotational speed (TRS) (1000 to 1800 rpm) with a constant feed rate of 85 mm/min with the tilt angle of 0°. The FSWed joint was characterized by mechanical properties and microstructural at room temperature and it was observed that all the welded joints produced a sound welded joint with a smooth surface except 1800 rpm. The maximum tensile strength (214.79 MPa), and micro-hardness (118) at the nugget zone was observed at tool rotation 1200 rpm and 1000 rpm respectively with constant traverse speed 85 mm/min and tilt angle 0°. The effect of tool rotation on FSW welded joint also improve the ductility of the welded joints at a certain limit, FSW welded joint with tool rotation 1200 rpm was more ductile than the other FSW welded joint due to fine grain structure. The grains size in the nugget zone at higher tool rotation (1200 rpm) was observed much finer (7.9 µm) than the other rotational speed. The minimum residual stress of 14 MPa was observed at TRS of 1200 rpm, whereas maximum residual stress of 98 MPa was observed at 1800 rpm.